A matrix rational Lanczos method for model reduction in large‐scale first‐ and second‐order dynamical systems. Issue 1 (18th November 2016) - Barkouki, H.; Bentbib, A.H.; Jbilou, K.
Summary: In the present paper, we describe an adaptive modified rational global Lanczos algorithm for model‐order reduction problems using multipoint moment matching‐based methods. The major problem of these methods is the selection of some interpolation points. We first propose a modified rational global Lanczos process and then we derive Lanczos‐like equations for the global case. Next, we propose adaptive techniques for choosing the interpolation points. Second‐order dynamical systems are also considered in this paper, and the adaptive modified rational global Lanczos algorithm is applied to an equivalent state space model. Finally, some numerical examples will be given.